2020
DOI: 10.11609/jott.5447.12.13.16924-16926
|View full text |Cite
|
Sign up to set email alerts
|

First report of mango leaf gall midge Procontarinia robusta Li, Bu & Zhang (Diptera: Cecidomyiidae) from India

Abstract: The present study reports a leaf gall midge, Procontarinia robusta Li, Bu & Zhang of Mango, Mangifera indica L. from India.  It is being reported for the first time from India.  Earlier, this species was reported from China, Indonesia and East Timor.  A brief diagnosis of its immature stages and coloured images are given to facilitate easy identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Nubs JX110976, JX110977, JX110978, and JX110979 (Figure 5). The genetic similarity of pests that infect mango trees in Bali with P. robusta is confirmed by the results of research by Vasanthakumar et al (2020) and Kolesik and Gagne (2020), who reported that P. robusta species is one of the causes of gall disease in mango plants. Mango plantations in Beijing, China were attacked by the pest Syringa reticulata subsp.…”
Section: Dna Barcodingmentioning
confidence: 58%
See 2 more Smart Citations
“…Nubs JX110976, JX110977, JX110978, and JX110979 (Figure 5). The genetic similarity of pests that infect mango trees in Bali with P. robusta is confirmed by the results of research by Vasanthakumar et al (2020) and Kolesik and Gagne (2020), who reported that P. robusta species is one of the causes of gall disease in mango plants. Mango plantations in Beijing, China were attacked by the pest Syringa reticulata subsp.…”
Section: Dna Barcodingmentioning
confidence: 58%
“…(Augustyn et al 2010;Singh 2018). Among these pests, the mango gall fly causes the most damage to crops in the field and is considered an important pest in various countries in the world, such as China (Jiao et al 2018), Northern Australia, Papua New Guinea (Kolesik et al 2009;Jiao et al 2018), India (Vasanthakumar et al 2020), and Pakistan (Karar et al 2021). The most common symptom shown by this pest attack is gall-shaped mango leaves (Augustyn et al 2013) which can interfere with plant metabolism and physiological processes during photosynthesis which adversely affects plant growth (Syawaluddin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation